Typification of four names of Dioscorea (Dioscoreaceae) from India - Pagare, Ravikiran S.; Arisdason, Wilson; Janarthanam, Malapati K. (Phytotaxa, 2021)
Lectotypes for Dioscorea nummularia var. belophylla [the basionym of Dioscorea belophylla], D. kalkapershadii, D. oppositifolia and D. velutipes are designated.